Structure of Pathogens Causing Invasive Mycoses and the Development of Their Resistance to Antifungal Drugs - A. V. Avtonomova; L. M. Krasnopolskaya (Антибиотики и Химиотерапия, 2025)
During the last decades, the number of cases of invasive mycoses has risen dramatically, and one of the reasons for that is the rise in the number of immunocompromised patients. The main causative agents of invasive mycoses are the pathogenic fungi from Candida and Aspergillus genera. The cases of invasive mycoses caused by the fungi from Mucorales order, Fusarium genus (sometimes from other taxa) also became more frequent. In 2022, WHO published for the first time a ranked list of fungal pathogens dangerous to human health, including the ones causing invasive mycoses. The most cases of invasive mycoses in intensive care units are caused by the causative agents from the Candida genus. The frequency of detection of Candida albicans as a causative agent has decreased from 70–80% in the end of 20th century to 40–60% in recent years. In contrast, the number of candidiasis caused by Nakaseomyces glabratus and Candida parapsilosis is growing. A limited number of drugs for systemic use from the polyenes, azoles, echinocandins, and flucytosine groups are used for treatment of invasive mycoses. The number of cultures resistant to antimycotics is increasing worldwide. The main factors of resistance to antimycotics among fungi are the general resistance of the species and long-term usage of such medications. Resistant or low-sensitive isolates of pathogenic fungi and the mechanisms of resistance have been identified for all used antimycotics. The strategy to overcome the problem of increasing cases of invasive mycoses should include the optimisation of treatment protocols for the invasive mycoses, the fundamental research of the mechanisms of resistance of pathogenic fungi, and the development of ways to overcome the resistance, including the search for the new antimycotics.